HYPERTENSION IS ASSOCIATED WITH BIGGER PROSTATE VOLUME AMONG BPH PATIENTS AT dr. SOEBANDI GENERAL HOSPITAL, JEMBER - Radiva Eryadana, Aqshal; Wahyudi, Septa Surya; Febianti, Zahrah (Indonesian Urological Association, 2023)
ABSTRACT Objective: Hypertension is one of BPH (Benign Prostate Hyperplasia) risk factors. This study was to compare the prostate volume of hypertensive-BPH patient and normotensive-BPH patient at Soebandi General Hospital Jember. Material & Methods: This is an observational analytic study with cross-sectional design conducted at Soebandi General Hospital, Jember. The data (blood pressure and prostate volume) were obtained from the medical records of BPH patients visiting the Urology Department during December 2021 until January 2022. They were analyzed with Independent T-test. Result: The results showed that there was a significant difference in prostate volume between hypertensive-BPH patients and normotensive BPH patients (p-value: 0.013). Among the BPH patients, the hypertensive groups had a bigger prostate volume than the normotensive groups. Conclusion: This study proves that hypertension is associated with bigger prostate volume among BPH patients at Soebandi General Hospital, Jember. Keywords: Independent T-test, prostate volume, blood pressure.